2017
DOI: 10.1177/0363546517730358
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Radiographic Outcomes Between Central and Lateral Lesions After Osteochondral Autograft Transplantation for Osteochondritis Dissecans of the Humeral Capitellum

Abstract: The clinical and radiographic outcomes after OAT associated with unstable OCD of the humeral capitellum were better for central lesions than for lateral lesions. However, satisfactory outcomes and a high rate of return to sports were obtained for unstable lateral lesions after OAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 41 publications
(73 reference statements)
0
33
0
Order By: Relevance
“…OAT has been widely used for OCD, and several experts have reported favorable clinical outcomes. 4,8,13,15,17,27,28,32 Maruyama et al 15 reported that in 33 elbows of patients aged ≤15 years who received OAT, which was the same as our technique, the Timmerman-Andrews score was 190 points, the total arc of elbow motion was 133°, and mean time to return to sports was 6.9 months. Based on the clinical outcomes of OAT after a mean of 3.5 years of follow-up, the elbow joint ROM and Timmerman-Andrews scores were similar to those from the current report.…”
Section: Discussionmentioning
confidence: 77%
“…OAT has been widely used for OCD, and several experts have reported favorable clinical outcomes. 4,8,13,15,17,27,28,32 Maruyama et al 15 reported that in 33 elbows of patients aged ≤15 years who received OAT, which was the same as our technique, the Timmerman-Andrews score was 190 points, the total arc of elbow motion was 133°, and mean time to return to sports was 6.9 months. Based on the clinical outcomes of OAT after a mean of 3.5 years of follow-up, the elbow joint ROM and Timmerman-Andrews scores were similar to those from the current report.…”
Section: Discussionmentioning
confidence: 77%
“…Patients were permitted to resume their respective throwing activities after 4 and 6 months postoperatively based on affected OCD lesion (central lesion, 4 months; lateral lesion, 6 months). 27…”
Section: Methodsmentioning
confidence: 99%
“…OAT has been proposed for reconstruction of articular surface defects and has shown good short-term results. 15,26,27,38,47 However, the OAT procedure requires harvesting of tissue from the asymptomatic knee joint. Thus, surgeons must thoroughly consider donor site morbidity (DSM).…”
mentioning
confidence: 99%
“…8,9,15 Although results after single-plug OG have been generally good, objective and quantitative evidence of graft healing on postoperative magnetic resonance imaging (MRI) scans has not been well-documented. Previous investigations have reported good radiologic healing in retrospective series, 2,7,12,17,19 but the criteria for radiologic healing are poorly defined. One underlying reason is the absence of a radiologic assessment tool specific for the post-OG elbow.…”
mentioning
confidence: 99%